Antioxidant capacity and lipid oxidation of alpaca sausages with red quinoa cooked Sous Vide - Calsin-Cutimbo, Marienela; Aro-Aro, Juan; Mayta-Barrios, Nury (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Currently, sausage consumption has been linked to health problems due to its high fatty acid and cholesterol content, forcing the use of low-fat meats, natural antioxidants, extenders, and new processing technologies to maintain its nutritional properties and reduce oxidation. The objective of this study was to evaluate the effect of red quinoa as an extender on the antioxidant capacity and lipid oxidation in alpaca sausages cooked sous vide at different temperatures. For the study, alpaca sausages were made by mixing ground alpaca meat, salt, animal fat, and extenders (raw quinoa, quinoa flour, cooked quinoa, and corn starch). The mixtures were cooked sous vide at 60 °C and 80 °C, and stored at 50 °C for 12 days, taking samples on days 1, 7, and 12, to determine the antioxidant capacity (ABTS method), lipid oxidation (TBARS method), pH, color, and texture. The results indicated that the highest values of antioxidant capacity were obtained in alpaca sausages with quinoa flour, causing a lower degree of lipid oxidation, indicated by the low TBARS value, in addition to the greater stability in the values of pH, luminosity (L*), redness (a*) and lower discoloration (b*), which can be attributed to the phenolic antioxidants of red quinoa. In conclusion, the use of red quinoa is an alternative because it can not only be used as an extender in sausage production, but also because it inhibits lipid oxidation and improves the antioxidant activity of the product.